LEGAL ASPECTS OF ANIMAL PROTECTION: INTERNATIONAL STANDARTS AND THE UKRAINIAN LEGISLATIVE FRAMEWORK - Pohrebniak, Mariia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose of the article is to characterize international and national legislation in the field of animal protection against cruelty. This research involves a comprehensive analysis and comparison of Ukrainian and international standards in the field of animal protection, as well as the study of such an important and relevant topic as the protection of animal rights. The methodological basis of the study lies in the analysis of Ukrainian legislation and international standards regarding animal protection to identify gaps and opportunities for further improvement of legal regulation in this area. Research methods: is aimed at analyzing the implementation of international standards into Ukraine’s domestic legislation and assessing the effectiveness of their practical application. Additionally, the study will examine the experience of European Union countries in this field to identify best practices and possible ways to improve Ukraine’s legislation. Results: the analysis of Ukrainian legislation and international standards revealed gaps in the implementation of animal protection measures and identified the need for legislative improvement to enhance living conditions and protect animals from cruelty. The results indicate the necessity for prompt and effective measures to ensure compliance with laws and international standards for wildlife protection. Discussion: the analysis of legislation and international standards highlights the importance of further improving animal protection legislation in Ukraine. Considering the identified gaps and shortcomings, it is important to develop and implement effective control mechanisms that will ensure compliance with norms and standards, as well as improve animal living conditions and prevent cruelty towards them.